The Influence of Cultural-Historical Determinants on Functional-Spatial Development of Rural Areas - Borucińska-Bieńkowska, Hanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article discusses selected issues regarding the influence of cultural-historical determinants on functional-spatial development of rural areas. Ecological, economic and social processes taking place in the last decades are examined in the context of the development of local self-governments and the rise of free market economy after Poland`s socio-economic transformation.
Keywords: rural areas; functional-spatial development; cultural-historical determinants; economics; ecological processes; social processes; obszary wiejskie; rozwój funkcjonalno-przestrzenny; uwarunkowania kulturowo-historyczne; ekonomia; ekologia; procesy społeczne